Enhanced bioavailability of lycopene when consumed as cis‐isomers from tangerine compared to red tomato juice, a randomized, cross‐over clinical trial. Issue 4 (10th March 2015) - Cooperstone, Jessica L.; Ralston, Robin A.; Riedl, Ken M.; Haufe, Thomas C.; Schweiggert, Ralf M.; King, Samantha A.; Timmers, Cynthia D.; Francis, David M.; Lesinski, Gregory B.; Clinton, Steven K.; Schwartz, Steven J.
<x xml:space="preserve">Abstract</x> Scope Tangerine tomatoes (Solanum lycopersicum) are rich in tetra‐cis‐lycopene resulting from natural variation in carotenoid isomerase. Our objective was to compare the bioavailability of lycopene from tangerine to red tomato juice, and elucidate physical deposition forms of these isomers in tomatoes by light and electron microscopy. Methods and results Following a randomized cross‐over design, subjects (n = 11, 6 M/5 F) consumed two meals delivering 10 mg lycopene from tangerine (94% cis) or red tomato juice (10% cis). Blood was sampled over 12 h and triglyceride‐rich lipoprotein fractions of plasma were isolated and analyzed using HPLC‐DAD‐MS/MS. Lycopene was crystalline in red tomato chromoplasts and globular in tangerine tomatoes. With tangerine tomato juice we observed a marked 8.5‐fold increase in lycopene bioavailability compared to red tomato juice (p < 0.001). Fractional absorption was 47.70 ± 8.81% from tangerine and 4.98 ± 1.92% from red tomato juices. Large heterogeneity was observed among subjects. Conclusion Lycopene is markedly more bioavailable from tangerine than from red tomato juice, consistent with a predominance of cis‐lycopene isomers and presence in chromoplasts in a lipid dissolved globular state. These results justify using tangerine tomatoes as a lycopene source in studies examining the potential health benefits of lycopene‐rich foods.